Advanced engineering mathematics with MATLAB - Harman, Thomas L.; Dabney, James B.; Richrt, Norman J. (Pacific Grove, CA : Brooks/Cole, 2000)
This book presents mathematical techniques for applications in engineering, physics, and applied mathematics.
Keywords: Matlab; Data processing; Engineering mathematics; MATLAB; Engineering mathematics -- Data processing